DUKUNGAN SOSIAL TERHADAP MATERNAL DEPRESSIVE SYMPTOMS - Inge Anggi Anggarini (IKesT Muhammadiyah Palembang, 2021)
Background: The postpartum period has a unique meaning for a woman having children will give a positive value. Playing the role of a mother creates a feeling of need which indirectly creates these positive feelings. The postpartum period is a transition period in which physical and psychological changes occur. Objective: to determine the relationship between social support and changes in maternal depressive symptoms. Methods: This research design is a descriptive correlative research type with a cross sectional approach. The number of samples was 59 respondents using consecutive sampling technique. Collecting data using questionnaires and data analysis using chi-square. Results: The results showed that there was a significant relationship between social support factors and maternal depressive symptoms (0.04 < 0.05). Conclusions: Social support from husband and family can reduce maternal depressive symptoms in postpartum mother.